Leishmania tarentolae as Potential Live Vaccine Co-Expressing Distinct Salivary Gland Proteins Against Experimental Cutaneous Leishmaniasis in BALB/c Mice Model - Lajevardi, Mahya Sadat; Gholami, Elham; Taheri, Tahereh; Sarvnaz, Hamzeh; Habibzadeh, Sima; Seyed, Negar; Mortazavi, Yousef; Rafati, Sima (Frontiers in Immunology, 2022)
Leishmaniasis is a neglected vector-borne disease caused by Leishmania parasites transmitted through the infected sand flies bite. Current treatments are limited, partly due to their high cost and significant adverse effects, and no human vaccine is yet available. Sand flies saliva has been examined for their potential application as an anti-Leishmania vaccine. The salivary protein, PpSP15, was the first protective vaccine candidate against L. major. Additionally, PsSP9 was already introduced as a highly immunogenic salivary protein against L. tropica. Herein, we aimed to develop an effective multivalent live vaccine to control Cutaneous Leishmaniasis induced by two main species, L. major and L. tropica. Hence, the two above-mentioned salivary proteins using T2A linker were incorporated inside the L. tarentolae genome as a safe live vector. Then, the immunogenicity and protective effects of recombinant L. tarentolae co-expressing PpSP15 and PsSP9 were evaluated in pre-treated BALB/c mice with CpG in combat with L. major and L. tropica. Following the cytokine assays, parasite burden and antibody assessment at different time-points at pre and post-infection, promising protective Th1 immunity was obtained in vaccinated mice with recombinant L. tarentolae co-expressing PpSP15 and PsSP9. This is the first study demonstrating the potency of a safe live vaccine based on the combination of different salivary proteins against the infectious challenge with two different species of Leishmania.